PENERAPAN ASAS KEBEBASAN BERKONTRAK TERHADAP PERJANJIAN WARALABA BENTUK USAHA INDOMART DI SAMARINDA - Oktofianus Siki (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
abstract In the Indonesian economy, one area that is quite prominent in trade. It has three main activities, namely the economic system of Production, Distribution and Consumption. One way of distributing the effort to expand internationally is through licensing, as an alternative attempt to get closer to consumers in the host country as well as to reduce the impact of high export transport costs, as well as the risk of loss of products from the market as a result of transportation risks and possible embargo done politically. 2) License is a temporary form of entitlement which can be exclusive or non - exclusive. Granting this right then felt not enough, if the license grantor intends to do a "refresher total" is not only in the form of rights, but also obligations - the obligation to obey and execute all and every command issued including the system operational implementation of the licensed activities 3 ). For that, they begin to develop the franchise. Franchise in Indonesian paired with the word waralabae set out in Government Regulation No. 42 of 2007 and Decree of the Minister of Industry and Trade of the Republic of Indonesia No. 259 / MPP / Kep / 7/1997 About Conditions and Procedures Implementation Franchise Registration.